Kuat Tekan Beton Dengan Agregat Kasar Batu Gamping Untuk Berbagai Macam Fas 0,34%; 0,34; 0,36; 038; 0,40 - Erdy Hartanto (Jurusan T.Sipil Fakultas Teknik UMy, 2013)
Kuat Tekan Beton Dengan Agregat Kasar Batu Gamping Untuk Berbagai Macam Fas 0,34%; 0,34; 0,36; 038; 0,40